MCPyV-Negative Merkel Cell Carcinoma In Situ Associated With Immunosuppression. (April 2023) - Mazumder, Anika; Khoshnoodi, Pooria; Gruber, Jessica; Burkemper, Nicole M.
Abstract: Merkel cell carcinoma (MCC) is a rare and aggressive cutaneous neoplasm that is almost always intradermal. Immunosuppression increases the risk of MCC, which is believed to be due to increased susceptibility to Merkel cell polyomavirus (MCPyV). Intraepidermal MCC, or MCC in situ (MCCis), is extremely rare and usually associated with other cutaneous lesions. Here, we describe a case of MCPyV-negative MCCis arising in an immunocompromised patient. This case adds to only 9 previously reported cases of MCCis without a coexisting neoplasm and suggests that immunosuppression can lead to MCCis by mechanisms other than MCPyV. Although previously reported cases of MCCis demonstrated excellent prognosis, local recurrence and metastasis are still possible. Prognostication, treatment, and follow-up of MCCis should be similar to MCC.